1995
DOI: 10.2307/2399832
|View full text |Cite
|
Sign up to set email alerts
|

The Biology and Systematics of Fuchsia in the South Pacific

Abstract: THE BIOLOGY AND SYSTEMATICS OF FUCHSIA IN THE SOUTH PACIFIC 1nly lour species of Fuchsia lli.it are nol native to the New World, three occurring on \ev\ Zealand ; laliiln Hi-bilo> m< ii i -i h.'se laxa are examined here in detail, including known and i i phenology, habitats, pollination, dispersal, cytology, hybridization, and evolutionary relationships. I basal position of F. jtiocinnln-ns in the cladc of South Pacific fuchsias and its large suite of uni< s recognized as a new section, Procumbentes, within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 1 publication
1
23
0
Order By: Relevance
“…Fuchsia excorticata has heterogametic sex determination, whereby females produce 50 : 50 hermaphrodite : female offspring and hermaphrodites produce all-hermaphrodite offspring (Godley and Berry 1995). Thus, the maintenance of gynodioecy depends on the success of females as seed parents.…”
Section: Discussionmentioning
confidence: 99%
“…Fuchsia excorticata has heterogametic sex determination, whereby females produce 50 : 50 hermaphrodite : female offspring and hermaphrodites produce all-hermaphrodite offspring (Godley and Berry 1995). Thus, the maintenance of gynodioecy depends on the success of females as seed parents.…”
Section: Discussionmentioning
confidence: 99%
“…1996;Webb 1999;Merrett 2007). \&F excorticata, male sterility is controlled by a single dominant gene with females being heterogametic (Godley & berry 1995), so hermaphrodites produce only hermaphrodite offspring, while females produce offspring with a 50:50 sex ratio. Hence, the population should approach 50% females only if hermaphrodites never reproduce successfully by seed.…”
Section: Discussionmentioning
confidence: 99%
“…The 12 × 5 mm fruits are a berry containing c. 300-600 small seeds in four locules (Godley & berry 1995). Fruits ripen from green through maroon to purple-black.…”
Section: Study Speciesmentioning
confidence: 99%
“…The following 10 species are usually winter deciduous (adults are entirely leafless, or nearly so, towards the end of winter): Moore & Irwin (1978) suggested that this species retains leaves over winter in the north, but completely deciduous populations have been recorded in the Auckland area (Esler in Godley & Berry 1995).…”
Section: Deciduous and Semideciduous Speciesmentioning
confidence: 99%
“…Fuchsia magellanica of southern South America is deciduous, but is in a different section to the New Zealand Fuchsia, which probably diverged over 50 m.y. ago from the rest of the genus (Sytsma et al 1991;Godley & Berry 1995). It is highly probable that the New Zealand Fuchsia immigrated from Australia, where the genus appeared some millions of years earlier (Martin 2003), but it is unlikely that it was deciduous at this time because of the prevailing subtropical climates.…”
Section: Biogeographical Relationshipsmentioning
confidence: 99%